Monitoring Supraglacial lakes Formation and Risk of Outburst Flooding in the Himalayan Cryosphere of Pakistan - Ashraf, Arshad; Rustam, Manshad (International Journal of Environment, 2020)
The dramatic rise in warm temperatures in the Himalayan region has caused the formation and expansion of numerous supraglacial lakes, some of which pose a serious flood hazard for the downstream communities. In this study, we have investigated the risk of flood hazards associated with supraglacial lakes in the Hindu Kush, Karakoram and Himalayan ranges of Pakistan using Landsat 8 OLI (Operational Land Imager) data of 2013 and field observations. Among the total of 438 supraglacial lakes, the majority were identified in the Karakoram (378) followed by the Hindu Kush range (39). The concentration of lakes was high within 3500-4000 m elevation (168) followed by 4000-4500 m elevation range (116). The lakes had shown more than a two-fold increase during the 2001-2013 period in the three mountain ranges. The increase in lake number was pronounced over valley glaciers likely due to increasing hydro-glacial activity under changing climate. Two types of supraglacial lakes were identified based on geographic characteristics, for example those rolling over glaciers surface away from the margins (called rolling supraglacial lakes ‘RSLs’) and the lakes found near the margins of glaciers mostly stationary in nature (called static supraglacial lakes ‘SSLs’). Most of the glacial lakes outburst flood (GLOF) events have been observed from SSLs in this region. However, the hydrodynamic process exaggerating the risk of GLOF from supraglacial and englacial lakes needs in-depth research for effective disaster risk reduction in this region in future.